Investment Incentives in Environmental Projects in Indonesia: An Analysis of Legal Potentials & Challenges - Harris, Richard; Shahrullah, Rina Shahriyani; Nurlaily, Nurlaily (Journal of Judicial Review, 2024)
Environmental sustainability is an issue that needs serious support, not just from within the exclusive realm of legal environmental protection, but also investment law, which fosters better partnership between the government, local communities, and the private sector. In an effort to promote sustainability, Indonesia can’t solely rely on the prevention of environmental degradation, but also has to constantly seek for ways to navigate around climate change concerns, and strive for innovations that can solve environmental problems, particularly through environmental projects. This research aims to analyze the potential of investment incentives in promoting investments in environmental projects in Indonesia. By using normative legal research method and statutory approach, analysis of this research finds that there is a lack of environmental constitutional will, manifested within the Investment Law, along with the lack of nation-wide regulation support to provide incentives for environmental projects. Analysis of this study suggests that the revision of the Investment Law can help fill the normative gap, along with streamlining nation-wide efforts in realizing Sustainable Development Goals.